2010
DOI: 10.1021/jp105296c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Crowding by Dextrans on the Hydrolysis of N-Succinyl-l-phenyl-Ala-p-nitroanilide Catalyzed by α-Chymotrypsin

Abstract: Traditionally, studies on the diffusion-controlled reaction of biological macromolecules have been carried out in dilute solutions (in vitro). However, in an intracellular environment (in vivo), there is a high concentration of macromolecules, which results in non-specific interactions (macromolecular crowding). This affects the kinetics and thermodynamics of the reactions that occur in these systems. In this paper, we study the crowding effect of large macromolecules on the reaction rates of the hydrolysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
94
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 50 publications
9
94
2
Order By: Relevance
“…They showed that for samples of Dextrans of about 20% (w/w) the reaction rates decrease with the increase of Dextran size: a decrease of about 2, 5 and 7-fold was observed for Dextrans of 15-70, 200 and 500 kDa, respectively However, it is in contrast with the results showed in our previous works 37,41 and with the results of Minton et al 2,[8][9][10][11][12] . In all these works, only excluded volume but not obstacle size was presented as a major factor influencing enzymatic reactions occurring in reaction media crowded by macromolecules.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…They showed that for samples of Dextrans of about 20% (w/w) the reaction rates decrease with the increase of Dextran size: a decrease of about 2, 5 and 7-fold was observed for Dextrans of 15-70, 200 and 500 kDa, respectively However, it is in contrast with the results showed in our previous works 37,41 and with the results of Minton et al 2,[8][9][10][11][12] . In all these works, only excluded volume but not obstacle size was presented as a major factor influencing enzymatic reactions occurring in reaction media crowded by macromolecules.…”
mentioning
confidence: 62%
“…In a situation of diffusion control, an increase in ‫ܭ‬ ୫ value can be expected since the bimolecular constant (݇ ଵ ) will decrease with the crowding [45][46][47] . In the literature, there are few works that report this situation 21,37,[45][46][47] . In these reported cases, a high diffusion resistance in the sample is responsible of a ‫ܭ‬ ୫ increase with Dextran concentration.…”
mentioning
confidence: 99%
“…In contrast, to account for the usual greater size of the crowding molecules and to analyse the effect of the relative crowder size in the diffusion-reaction process, four different obstacles sizes have been considered (see Fig. 1 Then, for a typical enzymatic reaction [33], with…”
Section: Simulation Algorithmmentioning
confidence: 99%
“…However, after the pioneering work of Laurent in 1971 [21], quite a few studies have explored the effects of crowding on enzyme catalysis, even in vitro [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation